Jeans modelling of the Milky Way’s nuclear stellar disc - Sormani, Mattia C.; Magorrian, John; Nogueras-Lara, Francisco; Neumayer, Nadine; Schönrich, Ralph; Klessen, Ralf S.; Mastrobuono-Battisti, Alessandra (Monthly notices of the Royal Astronomical Society, 2020)
The nuclear stellar disc (NSD) is a flattened stellar structure that dominates the gravitational potential of the Milky Way at Galactocentric radii $30 \lesssim R \lesssim 300\, {\rm pc}$. In this paper, we construct axisymmetric Jeans dynamical models of the NSD based on previous photometric studies and we fit them to line-of-sight kinematic data of the Apache Point Observatory Galactic Evolution Experiment (APOGEE) and silicon monoxide (SiO) maser stars. We find that (i) the NSD mass is lower but consistent with the mass independently determined from photometry by Launhardt et al. Our fiducial model has a mass contained within spherical radius $r=100\, {\rm pc}$ of $M(r\lt 100\, {\rm pc}) = 3.9 ± 1 × 10^8 \, \rm M_\odot$ and a total mass of $M_{\rm NSD} = 6.9 ± 2 × 10^8 \, \rm M_\odot$. (ii) The NSD might be the first example of a vertically biased disc, i.e. with ratio between the vertical and radial velocity dispersion σz/σR > 1. Observations and theoretical models of the star-forming molecular gas in the central molecular zone suggest that large vertical oscillations may be already imprinted at stellar birth. However, the finding σz/σR > 1 depends on a drop in the velocity dispersion in the innermost few tens of parsecs, on our assumption that the NSD is axisymmetric, and that the available (extinction corrected) stellar samples broadly trace the underlying light and mass distributions, all of which need to be established by future observations and/or modelling. (iii) We provide the most accurate rotation curve to date for the innermost $500\, {\rm pc}$ of our Galaxy.
Gesehen am 11.01.2021